Asas Kebebasan Berkontrak Perjanjian Sewa Menyewa Tanah (Analisis Putusan Mahkamah Agung Nomor 3693 K/Pdt/2020). - Walangitan, Semuel; Taqiyah, Lutfiatut (LITERATUS, 2024)
Land is a very basic need for human life. Humans live and carry out activities on land, so it can be said that almost all human life activities, both directly and indirectly, always require land. In this case, the application of the principle of contract can also be linked to the discussion of the author's thesis, namely the principle of freedom of contract, which can be reviewed in Article 1321 of the Civil Code, as the content of this legal rule is: "that no agreement is valid if the agreement was given due to mistake, or obtained by coercion. or fraud.”. The problem or violation of the rental agreement carried out by the Defendants A. Miski Hifayat and friends with SAODA ALI as the Plaintiff basically started with the Plaintiff receiving money from Defendant I, then the Plaintiff was required to sign a receipt which only contained the nominal amount of money borrowed, Meanwhile, the description of the payment was filled in by Defendant I himself, namely "extension of contract for empty yard land". The Panel of Judges of the Supreme Court forwarded the Decision of the Surabaya High Court dated January 22 2020, Case Number 867/Pdt.G./2019/PT Surabaya. Meanwhile, in the main case, the Panel of Judges, in its decision stated: 1) Rejected the cassation petition from the cassation petitioner SAODA ALI, referred to as also SA'ODA, 2) Sentencing the Cassation Petitioner to pay case costs at the cassation level in the amount of Rp. 500,000.00 (five hundred rupiah) Decision Number 3693/K/Pdt/2020. The research method applied by the author is normative legal research or library legal research methods. In this decision, the author is of the opinion that there were irregularities or inconsistencies in the two-way relationship in question, namely the relationship between Plaintiff Saoda Ali, and Defendant A. Miski Hifayat and friends. The Supreme Court made a mistake in determining the decision by not considering the causes and effects of the land lease agreement. (Half of Gladak Pakem Market) in the relationship between Plaintiff Saoda Ali, and the evidence should be that there are acts that violate the law in Article 1321 of the Civil Code which were carried out by the Cassation Respondent in his own settlement. This evidence is one of the basic things that legal justice must be applied which should be owned and obtained by Plaintiff Saoda Ali